POZZOLANIC PROPERTIES OF GLASS POWDER IN CEMENT PASTE - Norsuzailina, Sutan; Nafisa, Tamanna; Tuladhar, Rabin; Teo, Delsye Ching Lee; Ibrahim, Yakub (UNIMAS Publisher, 2016)
– This paper investigates the formation of Calcium Silicate Hydrate (C-S-H) as a product of pozzolanic reactions in a cement paste with cement partially replaced with crushed recycled glass at the rate of 10% and 20%. Three different particle sizes for crushed glass used in this study were in the range of 150-75µm, 75-38µm and lower than 38µm; and a water to cement ratio of 0.45 was used for all specimens. This study showed that the formation of Calcium Hydroxide Ca(OH)2 is decreased while the formation of C-S-H is increased simultaneously at 90 days for 75-38µm and <38µm glass powder. The use of waste glass as a partial cement replacement improves the cement strength through the formation of C-S-H due to the pozzolanic reaction with Ca(OH)2 improving the strength of the morta.